Strategi manajemen risiko sebagai upaya mitigasi kerugian pada perusahaan - hidayat, moh ahsanul (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the implementation of reputational risk management in enhancing customer trust in Islamic banking. Reputation is a critical and vulnerable asset, particularly due to the requirement to comply with Sharia principles, which form the foundation of customer trust. This research adopts a qualitative approach using a literature review method, examining various sources related to risk management, corporate governance, and customer behavior. The findings indicate that effective reputational risk management consists of four main stages: risk identification, assessment, monitoring, and control. Its implementation is supported by the role of the Sharia Supervisory Board, the application of Good Corporate Governance (GCG), and proactive and transparent communication strategies. Factors influencing reputational risk include internal aspects such as Sharia compliance, service quality, financial performance, and managerial ethics, as well as external factors such as digital media, regulatory changes, and macroeconomic conditions. Case studies demonstrate that failure to manage reputational risk can reduce customer trust and threaten banking stability. Conversely, effective management enhances customer loyalty and attracts new customers. Therefore, reputational risk management plays a vital role in creating sustainable competitive advantages in Islamic banking.